2019
DOI: 10.3390/su11092626
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance Analysis of Cement Production with CO2 Capture and Storage Technology in a Life-Cycle Perspective

Abstract: Cement manufacturing is one of the most energy and CO2 intensive industries. With the growth of cement production, CO2 emissions are increasing rapidly too. Carbon capture and storage is the most feasible new technology option to reduce CO2 emissions in the cement industry. More research on environmental impacts is required to provide the theoretical basis for the implementation of carbon capture and storage in cement production. In this paper, GaBi software and scenario analysis were employed to quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A life-cycle assessment (LCA) is a method for assessing all the potential environmental impacts of a product, process, or activity over its entire life cycle [104]. Several LCA studies have focused on the sustainability of concrete [105,106].…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…A life-cycle assessment (LCA) is a method for assessing all the potential environmental impacts of a product, process, or activity over its entire life cycle [104]. Several LCA studies have focused on the sustainability of concrete [105,106].…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…Some studies have evaluated adapting power sector applications to the cement sector, which we focus on here due to its non-energy derived emissions. The fraction of CO2 in flue gas from cement production, ranging from 15 to 30 mol%, is higher than the fraction found in flue gas from power plants [81,127]. Yet, CCUS solutions for power plants are not directly transferrable to cement production due to significant differences in equipment, processes and chemical/thermal reactions [128].…”
Section: Other Carbon Capture and Utilization Or Storage Opportunitiesmentioning
confidence: 99%
“…Reports have projected CCUS implementation in cement production plants to begin in 2030, and as such, a rigorous understanding of the technology and environmental impacts is required [129]. Several studies analyzing post-combustion CCUS reported it leading to lower GHG emissions than traditional cement production, but driving harmful increases for human health impacts [45,80,81,130], thus potentially shifting the problem from CO2 emissions to another impact category. Further, the use of CO2 captured from power plants in CCUS within concrete has been explored, but recent findings suggest a loss of mechanical strength could result in some of these technologies leading to higher CO2 emitting systems than conventional concrete [131].…”
Section: Other Carbon Capture and Utilization Or Storage Opportunitiesmentioning
confidence: 99%
“…Consequently, an important effort has been made to improve energy efficiency over time, with reduction around 30% of the energy consumed to produce clinker since the 1970s [15]. In addition, the use of alternative fuels yields economic savings for companies in this sector [16] and they are an interesting approach to tackle the environmental impact generated [17].…”
Section: Introductionmentioning
confidence: 99%